THE IMPACT OF WEB PAGE ACTIVITIES ON UZBEK SCHOOL PUPILS' EFL GRAMMAR PROFICIENCY (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This paper explores the impact of web page activities on Uzbek school pupils' EFL grammar proficiency. By examining various types of web-based activities, including interactive exercises, grammar games, multimedia content, and collaborative tools, the study highlights their benefits in enhancing grammar skills. Empirical evidence and case studies from Uzbek schools demonstrate significant improvements in students' grammar proficiency through the use of these digital tools. The paper provides practical recommendations for integrating web page activities into the EFL curriculum, emphasizing the need for high-quality resources, teacher training, equitable access, collaborative learning environments, and continuous progress monitoring.